2012
DOI: 10.1007/s10530-012-0250-9
|View full text |Cite
|
Sign up to set email alerts
|

Massive invasion of Arctodiaptomus dorsalis (Copepoda, Calanoida, Diaptomidae) in Philippine lakes: a threat to Asian zooplankton biodiversity?

Abstract: A study originally intended to update the systematics and zoogeography of calanoid copepods in Philippine lakes has led to the discovery of an invasion by the Neotropical Arctodiaptomus dorsalis. It now occurs in 18 out of 27 lakes in the archipelago. Only four of the 12 previously recorded native and endemic calanoids have been encountered in the lakes, which may indicate that most have been displaced by A. dorsalis, although a general deterioration of water quality by fish culture may also have contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 9 publications
3
39
0
Order By: Relevance
“…Zooplankton was collected by performing four vertical net hauls using a conical plankton net (mesh size, 80 µm; mouth diameter, 30 cm) at a pelagic site (depth, 40 m) in Lake Taal, Philippines (14°00′40.6″N, 121°05′19.1″E), where A. dorsalis was previously documented (Papa et al 2012a, b). In addition, one liter each of lake water from depths of 0, 5, 10, 20, 30, and 40 m was collected with a water sampler and then combined for use as the culture medium.…”
Section: Field Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Zooplankton was collected by performing four vertical net hauls using a conical plankton net (mesh size, 80 µm; mouth diameter, 30 cm) at a pelagic site (depth, 40 m) in Lake Taal, Philippines (14°00′40.6″N, 121°05′19.1″E), where A. dorsalis was previously documented (Papa et al 2012a, b). In addition, one liter each of lake water from depths of 0, 5, 10, 20, 30, and 40 m was collected with a water sampler and then combined for use as the culture medium.…”
Section: Field Collectionmentioning
confidence: 99%
“…Recent studies also showed that there has been a massive invasion of A. dorsalis in 18 out of 27 lakes investigated in the Philippines (Papa et al 2012a). Introduction of this spe-cies may have been through ship drinking water reserves dumped into Laguna de Bay (Tuyor & Baay 2001) which was then, through aquaculture practices, dispersed to other parts of the country (Papa et al 2012a). Recent studies by Metillo et al (2014) and Rizo et al (2015) added five more new locality records of A. dorsalis in the Bicol region of Luzon Island and Lake Lanao in Mindanao Island.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations